Sampling plan for using a motorized penetrometer in soil compaction evaluation - Lindolfo Storck; Sarha G. K. Kobata; Betania Brum; André B. Soares; Alcir J. Modolo; Tangriani S. Assmann (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to estimate the size of blocks of observations of resistance to penetration, obtained by a motorized digital penetrometer, and the number of blocks with semi-amplitude of the confidence interval between 5 and 20% of the mean penetration resistance, for different soil depth ranges and cone diameters. Data were collected in two contrasting plots of a crop-livestock integration experiment, located in Abelardo Luz, SC, Brazil. Ten blocks were delimited and the resistance to penetration was determined in 20 points spaced by 20 cm, using a motorized digital soil penetrometer. To estimate the mean of resistance to penetration, 12 blocks of four points per experimental plot should be used for a semi-amplitude of the confidence interval equal to 10% of the mean (1 - p = 0.95). Twenty random points may be sampled to estimate mean of penetration resistance for a semiamplitude confidence interval of 10% of the man (1 - p = 0.95). The sample size for the layer of 0-10 cm is larger than in the deeper layers (0-20, 0-30 and 0-40 cm) and smaller for cones with larger diameter.